Building up the database of the Level-2 Java Sea Ecoregion based on physical oceanographic parameters. (July 2018) - Simanjorang, J E; Pranowo, W S; Sari, L P; Purba, N P; Syamsuddin, M L
Abstract: The Java Sea (JS) is one of the sea with unique characteristic with especially in biodiversity and oceanographic condition. The purpose of this research is to identify the EL into level 2 in Java Sea based on oceanographic condition. The Java Sea, which covers an area of 467, 000 Km 2 with an average depth of 50m, is located on the Southeastern part of the Sunda Shelf. This research uses the temperature and salinity data provided by the INDESO, the sea surface height (SSH) data downloaded from the HYCOM website, and the level 2 Java Sea ecoregion shape file data from the Indonesian seas delineation team. The physical oceanographic conditions of the level 2 Java Sea ecoregions are influenced by the moonsun and their respective geographical positions. The results showed that the distribution of temperature, sea current, salinity, and Sea Surface Height differed in each Java Sea Ecoregion level 2 because it is influenced by the geographical and astronomical location of each Java Sea Ecoregion level and influenced by the monsoon that exists over Indonesia. In the east of Java Sea influence from Makassar Strait and in the west affected by Karimata Strait. Within the region, EL 6.1. (Sunda Strait), the physical oceanography condition is slightly different from other Java EL because it is strongly influenced by the Indian Ocean.